Overlooked 4Q51 Fragments - Tigchelaar, Eibert J. C. (Textus, 2023)
This short note lists the 4Q51 fragments that were excavated from Qumran Cave 4 and proposes that four hitherto unidentified fragments belong to 4Q51.